Highly Sensitive MoS2–Indocyanine Green Hybrid for Photoacoustic Imaging of Orthotopic Brain Glioma at Deep Site - Liu, Chengbo; Chen, Jingqin; Zhu, Ying; Gong, Xiaojing; Zheng, Rongqin; Chen, Ningbo; Chen, Dong; Yan, Huixiang; Zhang, Peng; Zheng, Hairong; Sheng, Zonghai; Song, Liang (Nano-Micro Letters, 2018)
Photoacoustic technology in combination with molecular imaging is a highly effective method for accurately diagnosing brain glioma. For glioma detection at a deeper site, contrast agents with higher photoacoustic imaging sensitivity are needed. Herein, we report a MoS2–ICG hybrid with indocyanine green (ICG) conjugated to the surface of MoS2 nanosheets. The hybrid significantly enhanced photoacoustic imaging sensitivity compared to MoS2 nanosheets. This conjugation results in remarkably high optical absorbance across a broad near-infrared spectrum, redshifting of the ICG absorption peak and photothermal/photoacoustic conversion efficiency enhancement of ICG. A tumor mass of 3.5 mm beneath the mouse scalp was clearly visualized by using MoS2–ICG as a contrast agent for the in vivo photoacoustic imaging of orthotopic glioma, which is nearly twofold deeper than the tumors imaged in our previous report using MoS2 nanosheet. Thus, combined with its good stability and high biocompatibility, the MoS2–ICG hybrid developed in this study has a great potential for high-efficiency tumor molecular imaging in translational medicine. Highlights: 1 MoS2 nanosheets was covalently conjugated with indocyanine green (ICG) by facile mixing ICG-Sulfo-NHS and MoS2 nanosheets. 2 The 3.5 mm imaging depth demonstrated in this study is one of the deepest among all the glioma photoacoustic imaging research reported so far by using the nanoprobe in the NIR I spectral region. 3 The design and validation of the MoS2–ICG hybrid bring up an effective strategy for synthesizing highly sensitive photoacoustic nanoprobes, i.e., by covalently conjugating optical dyes with transition metal dichalcogenides.